Polymeric micelles-mediated photodynamic therapy - de Santana, Willian Max O.S. [UNESP]; Pochapski, Daniel José [UNESP]; Pulcinelli, Sandra H. [UNESP]; Fontana, Carla Raquel [UNESP]; Santilli, Celso V. [UNESP] (Elsevier, 2023)
Polymeric micelles (PM) have been demonstrating high potential as multifunctional therapeutic nanoplatforms for anticancer photodynamic therapy (PDT). PM increase photosensitizer (PS) accumulation in tumor tissues, thus improving its antitumor effect. The development of PM responsive to endogenous (e.g., pH, reducing agents, and hypoxia) or exogenous (e.g., light) stimuli makes these polymeric structures even more versatile, since the delivery of PS to the target tissue occurs with good spatio-temporal control. This chapter covers the application of PM in PDT, focusing on targeting and stimulus-responsiveness release strategies. Our discussion will be based on the physical-chemical properties of the PM and the interaction of these carriers with biological systems.
Keywords: cancer therapy; nanocarriers; organic nanoparticles; Photodynamic therapy; polymeric micelles; polymeric nanoparticles; stimuli-responsive nanoparticles